PENGARUH KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP EFFECTIVE TAX RATE PADA BADAN USAHA MILIK NEGARA (BUMN) - Rani Faradilla; Anies Lastiati (Universitas Trilogi, 2022)
This study has a purpose, namely to determine the effect of independent commissioners and audit committees on the effective tax rate (ETR). The results of this study indicate that the independent commissioner has no effect on the effective tax rate (ETR), which means that the existing independent commissioner only meets the provisions of existing regulations and does not have an impact on tax policy. weak tax payments and audit committees have a negative effect on the effective tax rate (ETR), which means that the more audit committees with accounting and/or finance backgrounds, the lower the ETR, the greater the number of audit committees with accounting and/or tax backgrounds, the higher as well as tax avoidance. This study uses a sample of companies in BUMN for the period 2017 – 2019 with a purposive sampling method.